Voorzitter (midden in de verticale rij) van de afdeling Lemelerveld van het NKV. Serie van 2 foto's - Schie, Rinus van,
Voorzitter (midden in de verticale rij) van de afdeling Lemelerveld van het NKV. Serie van 2 foto's.